Lung Histopathology in Baclofen Intoxication - O. L. Romanova; D. V. Sundukov; M. A. Golubev; M. L. Blagonravov; A. V. Ershov (Общая реаниматология, 2021)
The aim of the study: to assess the lung histopathology in acute intoxication with baclofen alone and its combination with alcohol (in the same dose) 3 hours after the ingestion.Materials and methods. The study was performed on 15 male Wistar rats weighing 290-350 g and aged 20 weeks. The animals were divided into 3 groups, 5 animals each: control group that included intact rats; Group 1 composed of rats received baclofen alone; Group 2 that included rats received a combination of baclofen and ethanol. Baclofen was administered orally at a dose of 85 mg/kg animal weight under anesthesia (chloralose), and 40% ethanol, 7 ml/kg animal weight, was orally administered along with baclofen at the same dose. Animals of all groups were sacrificed after 3 hours by overdosing anesthetic agent. Lung tissue samples were examined by light microscopy using a video system at x400 magnification. The following histological characteristics were evaluated: circulatory disorders (engorged capillaries and venules, hemorrhages in interalveolar septa and alveoli, sludge), atelectasis (including partial), emphysema, cellular response (increased WBCs in the interalveolar septal area), thickening of interalveolar septa due to edema, epithelial desquamation into bronchial lumen. The diameter of alveoli and thickness of interalveolar septa were measured.Results. Three hours after the baclofen administration, circulatory disorders in the lungs (engorged venules and capillaries, hemorrhages in the interalveolar septa, sludge), emphysema, atelectasis (complete and partial) as well as cellular response (leucocyte infiltration of interalveolar septa) were detected. In the Group 2, baclofen resulted in circulatory disorders (engorged venules and capillaries, sludge), emphysema, atelectasis (complete and incomplete), cellular response (infiltration with leukocytes), as well as fluid in the lumen of bronchioles. In Group 1, the alveolar diameter was significantly larger than in the control group and Group 2, while the thickness of the interalveolar septa was lower. In group 2, alveolar diameter was significantly less than in group 1, but still greater than in the control group. The thickness of the interalveolar septa in group 2 was significantly greater than in the control group and group 1.Conclusion. After administration of baclofen alone and in combination with ethanol, the following alterations were found in the lungs: circulation disorders (venular and capillary engorgement, sludge), increased vascular permeability because of developing hypoxia, leukocyte infiltration of interalveolar septa. The monitoring of morphological alterations may aid in evaluating the severity of pathological processes in intoxication with baclofen alone and in combination with ethanol and in determining the method of intoxication (baclofen alone or in combination with ethanol).